Design of Polymer‐in‐Salt Electrolyte for Solid State Lithium Battery with Wide Working Temperature Range. Issue 21 (2nd June 2022) - Bai, Shuai; Zhang, Xiangxin; Chen, Zhou; Lin, Junhong; Wang, Qiming; Zhang, Yining
Abstract: Poly(ethylene oxide) (PEO) is an appealing matrix for solid polymer electrolytes (SPEs) due to its superior lithium salt dissolution ability. However, while such PEO‐based SPEs generally exhibit high crystallinity at room temperatures (∼30 °C), which severely hinders the application of SPEs. In this work, a Polymer‐In‐Salt solid electrolyte with a three‐dimensional frame structure was designed and fabricated with PVDF membrane as the frame and PEO‐in‐LiTFSI as a filler (PPIS). PPIS exhibits high ionic conductivity of 4.5×10 −5  S m −1 and lithium transference number of 0.53 at room temperature with a wide electrochemical window beyond 5.5 V. Meanwhile, it exhibits excellent interfacial stability which can effectively suppress the growth of lithium dendrite. The assembled LFP/PPIS/Li solid‐state battery exhibits excellent rate performance and cycling stability at 30 °C and 60 °C. In addition, LFP/PPIS/Li pouch cell displays significant safety and functional flexibility. Abstract : A versatile preparation method of solid electrolyte with a wide working temperature range. Different from the traditional solid polymer electrolytes in Li + transport mechanism, ionic clusters provide a fast transport pathway to Li + in Polymer‐in‐Salt solid electrolyte. The prepared Polymer‐in‐Salt solid electrolyte exhibits good electrochemical performance over a wide temperature range. The prepared solid‐state pouch cell exhibits high safety and functional flexibility.